The evolution of craniofacial resection: A new workflow for virtual planning in complex craniofacial procedures. Issue 9 (September 2019) - Tel, Alessandro; Bagatto, Daniele; Tuniz, Francesco; Sembronio, Salvatore; Costa, Fabio; D'Agostini, Serena; Robiony, Massimo
Abstract: Complex craniofacial surgery has been later to take advantage of computerized planning than traditional maxillofacial procedures. Virtual reality, 3D model navigation, and bioengineering analyses have changed our approach to the surgical planning of craniofacial resection, increasing the benefits of surgery in terms of accuracy while decreasing complication rate. This study introduces a new workflow for 3D reconstruction, virtual model navigation, and alignment analyses, and demonstrates its successful application in a sample of four patients. A case of squamous cell carcinoma of the maxillary and ethmoid sinus in a 62-year-old patient is presented to evaluate the application of the workflow for a combined transfacial and transcranial resection. Results demonstrate that virtual surgical planning was successfully translated into navigational coordinates and reproduced in the operating room. While the literature provides a wide range of applications of virtual planning for traditional maxillofacial procedures, its introduction for complex craniofacial procedures remains difficult. The presented case shows that it is worth investigating the correlation between virtual reality planning and surgical accuracy for craniofacial resection, and related advantages in terms of surgical safety and improved prognosis.